2007
DOI: 10.1007/s00540-006-0444-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain-relieving effects of intravenous ATP in chronic intractable orofacial pain: an open-label study

Abstract: Intravenous ATP did not relieve non-neuropathic orofacial pain. However, it exerted slowly expressed but long-lasting analgesic and anti-allodynic effects in patients with neuropathic orofacial pain, especially in those suffering from neuropathic pain following pulpectomy and/or tooth extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…171 They found that ATP caused a reduction of the VAS scores for spontaneous pain and allodynia by 82%±15% and 74%±9% respectively. These beneficial effects of ATP outlasted the infusion period (for medians of 7 and 12 h respectively).…”
Section: 0 Atp and P2x Ion Channel Receptors Antagonists As Potentimentioning
confidence: 95%
“…171 They found that ATP caused a reduction of the VAS scores for spontaneous pain and allodynia by 82%±15% and 74%±9% respectively. These beneficial effects of ATP outlasted the infusion period (for medians of 7 and 12 h respectively).…”
Section: 0 Atp and P2x Ion Channel Receptors Antagonists As Potentimentioning
confidence: 95%
“…ATP is immediately decomposed in the blood into adenosine; intravenous administration of drugs causes an analgesic effect that is mediated by A1 receptors. Continuous drip infusion, for 2 hours or longer, at a rate of 5-6 mg/kg/h can provide temporary, dramatic relief of phantom tooth pain [ 1 ]. The effect is slow to begin, but its duration can be anywhere from several days to several weeks.…”
Section: Case Reportmentioning
confidence: 99%
“…Second, although the direct actions of adenosine and ATP on the vascular smooth muscle are vasodilation via A2A purinoceptors and vasoconstriction via P2X purinoceptors, respectively [24,25], both intravenous adenosine and ATP equally cause dose-dependent vasodilation and hypotension [26]. Third, although the direct actions of adenosine and ATP on the spinal cord are antinociception via A1 purinoceptors [1] and pronociception via P2X purinoceptors [7,8], respectively, both intravenous adenosine and ATP analogously relieve neuropathic pain [12][13][14][15]. Fourth, although adenosine and ATP are known to act as anti-infl ammatory and proinfl ammatory substances, respectively [25], our present data suggest an anti-infl ammatory rather than proinfl ammatory property of intravenous ATP, as described below.…”
Section: Discussionmentioning
confidence: 97%
“…However, intravenous ATP may reduce postoperative pain, analogous to adenosine, because ATP is converted to adenosine within seconds via the action of ectonucleotidases in the bloodstream [10,11]. Actually, we have recently found that intravenous infusion of ATP can alleviate neuropathic pain [12,13], analogous to adenosine [14,15]. To date, however, the effects of intravenous ATP on pain control during and/or after surgery have not been investigated in humans.…”
Section: Introductionmentioning
confidence: 98%